Current Online Learning Trends for Professionals and Entrepreneurs in Business - Delgado, Ivan (2025)
This article explores the trends in online learning and the influence of specific criteria in the selection of online courses among executives and entrepreneurs in the business sector. The use of artificial intelligence (AI) in online learning platforms has been a key factor in enhancing the personalization and adaptability of courses, resulting in higher student satisfaction and success. The study highlights the evolution and importance of online learning platforms, detailing their methods, popular courses, pricing, and flexibility, which contribute to their success in virtual education. Additionally, the integration of AI technologies has allowed for a deeper analysis of student interaction patterns, facilitating the identification of areas for improvement and the implementation of personalized interventions. The research underscores the need for continuous updates in both technological tools and educator skills to meet the growing demands of online education. The article concludes that virtual education has a scalable and continuously growing future, driven by its perceived benefits and the adoption of advanced technologies.